Enrolment of older adults with cancer in early phase clinical trials—an observational study on the experience in the north west of England. (9th June 2021) - Gomes, Fabio; Descamps, Tine; Lowe, Jessica; Little, Martin; Lauste, Rosie; Krebs, Matthew G; Graham, Donna; Thistlethwaite, Fiona; Carter, Louise; Cook, Natalie
Abstract: Introduction: older patients represent the majority of cancer patients but are under-represented in trials, particularly early phase clinical trials (EPCTs). Material and Methods: observational retrospective study of patients referred for EPCTs (January–December 2018) at a specialist cancer centre in the UK. The primary aim was to analyse the successful enrolment into EPCTs according to age (<65/65+). The secondary aims were to identify enrolment obstacles and the outcomes of enrolled patients. Patient data were analysed at: referral; in-clinic assessment and after successful enrolment. Among patients assessed in clinic, a sample was defined by randomly matching the older cohort with the younger cohort (1:1) by tumour type. Results: 555 patients were referred for EPCTs with a median age of 60 years, of whom 471 were assessed in new patient clinics (38% were 65+). From those assessed, a randomly tumour-matched sample of 318 patients (159 per age cohort) was selected. Older patients had a significantly higher comorbidity score measured by ACE-27 ( P  < 0.0001), lived closer to the hospital ( P  = 0.045) and were referred at a later point in their cancer management ( P  = 0.002). There was no difference in suitability for EPCTs according to age with overall 84% deemed suitable. For patients successfully enrolled into EPCTs, there was no difference between age cohorts (20.1 vs. 22.6% for younger and older, respectively; P =  0.675) and no significant differences in their safety and efficacy outcomes. Discussion: older age did not affect the enrolment into EPCTs. However, the selected minority referred for EPCTs suggests a pre-selection upstream by primary oncologists.